Measurement of mandibular growth using cone-beam computed tomography: a miniature pig model study. - Hsien-Shu Lin (Public Library of Science (PLoS), 2014)
The purpose of this study was to measure the long-term growth of the mandible in miniature pigs using 3D Cone-Beam Computerized Tomography (CBCT). The mandibles of the pigs were scanned monthly over 12 months using CBCT and the 3D mandibular models were reconstructed from the data. Seventeen anatomical landmarks were identified and classified into four groups of line segments, namely anteroposterior, superoinferior, mediolateral and anteroinferior. The inter-marker distances, inter-segmental angles, volume, monthly distance changes and percentage of changes were calculated to describe mandibular growth. The total changes of inter-marker distances were normalized to the initial values. All inter-marker distances increased over time, with the greatest mean normalized total changes in the superoinferior and anteroposterior groups (p<0.05). Monthly distance changes were greatest during the first four months and then reduced over time. Percentages of inter-marker distance changes were similar among the groups, reaching half of the overall growth around the 4th month. The mandibular volume growth increased non-linearly with time, accelerating during the first five months and slowing during the remaining months. The growth of the mandible was found to be anisotropic and non-homogeneous within the bone and non-linear over time, with faster growth in the ramus than in the body. These growth patterns appeared to be related to the development of the dentition, providing necessary space for the teeth to grow upward for occlusion and for the posterior teeth to erupt.